Habermas and Religious Communication: The Insufficiency of the Translation Proviso - Rhodin, Lars (Religions, 2017)
Much has been debated and written about the translation proviso, its implications, and its rationality. At its core, it is about communication and a transition in religious communication that means it can become secularly engaged. This paper argues that the theory of the translation proviso is insufficient to accommodate religious communication and, in order to support the arguments made, considers associated aspects of the work of Habermas, such as solidarity, tolerance and universalism, as well, of course, as communication. Considerations in this wider context lead to a growing awareness that the translation proviso and its prescriptive tendencies may be seen as being an ominous contradiction of much of the other work of Habermas and that, far from being postmetaphysical and postmodern, it may have elements of being a big idea'.